The barriers to medication error reporting by nurses and factors associated with it: a cross-sectional study in a tertiary hospital of south-west China - Dongmei Wu; Lu Yang; Hui Su; Cui Wang; Xueping Peng; Weizheng Song; Simin Yang (BMJ Open)
Objectives To explore the reporting barriers and related factors of medication errors among nurses in hospitals in China and provide a reference for safe medication management in hospitals.Design Cross-sectional, online survey.Setting Responses were collected online from September 2022 to November 2022 across a specific tertiary hospital in Chengdu, China.Participants Clinical registered nurse.Primary outcome measure Measure the Barriers to Medication Administration Error (MAE) Reporting Questionnaire, Face-Saving Scale, the Index of Hierarchy of Authority and the Working Environment Questionnaire. Independent sample t-test, correlation analysis and multiple linear regression analysis were performed to identify factors associated with the barriers to MAE reporting.Results 432 (97.30%) nurses responded. Nurses’ standardised scores of barriers to MAE reporting were 3.01 (SD=1.01); the fear dimension items have the highest standardised score of 3.42 (SD=1.11). Working environment is negatively correlated with barriers to MAE reporting (r=−0.201, p<0.01); face-saving (r=0.866, p<0.01) and index of hierarchy of authority (r=0.799, p<0.01) are positively correlated with barriers to MAE reporting. All three were the main influencing factors of barriers to MAE reporting, which could explain 82.4% of the barriers’ variance (R2=0.826, R2adj=0.824, F=253.665, p<0.001).Conclusions Nurses’ medication error reporting barriers mainly come from the fear of reporting consequences. The working environment is the protective factor of reporting barriers. Still, face-saving and the index of hierarchy of authority are the main risk factors. Improving the working environment may help reduce medication error reporting barriers. Still, more importantly, hospital managers need to take adequate measures to reduce nurses’ sense of face-saving and power distance, which may be more helpful in reducing the barriers to medication error reporting and improving hospital medication safety management.